The Influence of Occupational Health and Safety (OHS) on Employee Work Quality at PT Semen Tonasa, Pangkep Regency - Nurfadillah Nurfadillah; Edi Jusriadi; M.Yusuf Rendra Anggoro (Journal Social Society, 2026)
This study is urgent because improving Occupational Health and Safety (OHS) is crucial to enhancing employee work quality, productivity, and accident prevention in a high-risk industrial environment like PT Semen Tonasa. The study on the influence of occupational health and safety (OHS) on employee work quality at PT Semen Tonasa is important because employees are the organization’s main assets, and their performance is strongly affected by workplace conditions. The cement industry is a high-risk sector, making OHS not only a legal obligation but also a strategic effort to safeguard employee safety and enhance productivity. This research aims to determine the influence of occupational safety and occupational health on the quality of employee work at PT Semen Tonasa, Pangkep Regency. The type of data used is quantitative data obtained through distributing questionnaires to 59 respondents. Data collection through questionnaires distributed to respondents. The data analysis technique used is multiple linear regression with the help of the Statistical Package for the Social Sciences (SPSS) version 15.0 application. The research results show that the work safety variable (X1) does not have a positive and significant effect on work quality (Y), with a significance value of 0.397 > 0.05 and a t value of 0.854 < t table 2.003. Meanwhile, the occupational health variable (X2) has a positive and significant effect on work quality, as indicated by a significance value of 0.000 < 0.05 and a t value of 4.017 > t table 2.003. Simultaneously, work safety (X1) and work health (X2) have a significant effect on employee work quality with a significance value of 0.001 < 0.05 and a calculated F value of 8.386 > F table 3.16. Based on these results, it can be concluded that together occupational safety and health have a significant effect on the quality of employee work at PT Semen Tonasa.